2009
DOI: 10.1189/jlb.0609391
|View full text |Cite
|
Sign up to set email alerts
|

The axonal repellent, Slit2, inhibits directional migration of circulating neutrophils

Abstract: In inflammatory diseases, circulating neutrophils are recruited to sites of injury. Attractant signals are provided by many different chemotactic molecules, such that blockade of one may not prevent neutrophil recruitment effectively. The Slit family of secreted proteins and their transmembrane receptor, Robo, repel axonal migration during CNS development. Emerging evidence shows that by inhibiting the activation of Rho-family GTPases, Slit2/Robo also inhibit migration of other cell types toward a variety of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(137 citation statements)
references
References 58 publications
(110 reference statements)
11
126
0
Order By: Relevance
“…Slit2 binds to the Robo1 receptor on monocytes, macrophages, neutrophils, and dendritic cells (35)(36)(37). We observed that Robo1 is expressed on fibrocytes and macrophages and that incubating PBMCs with Slit2 led to reduced fibrocytes, but no obvious changes in Robo1 levels on macrophages (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…Slit2 binds to the Robo1 receptor on monocytes, macrophages, neutrophils, and dendritic cells (35)(36)(37). We observed that Robo1 is expressed on fibrocytes and macrophages and that incubating PBMCs with Slit2 led to reduced fibrocytes, but no obvious changes in Robo1 levels on macrophages (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…1 For example, some axon guidance molecules, such as slits [2][3][4] and ephrins, [5][6][7][8] have been shown to regulate immune cell migration. In addition, T-cell-antigenpresenting cell contact sites, the so-called 'immunological synapse', is structurally similar to the 'neurological synapse' that connects pairs of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In neuronal cells, Slit2 promotes recruitment of soluble Slit Robo GTPase-activating protein to the cytoplasmic tail of Robo-1, in turn preventing activation of the Rho family GTPases Rac and Cdc42 (20). We (17,21) and other investigators (14-16, 18, 19) showed that secreted Slit2 interacts with Robo-1 on the surface of human PBMC, neutrophils, VSMC, and monocytes to inhibit migration of these cells toward diverse inflammatory chemoattractant cues both in vitro and in vivo. We observed that binding of Slit2 to Robo-1 prevented activation of Cdc42 and Rac, thereby preventing the actin polymerization and cell polarization necessary for directional migration of leukocytes (17).…”
Section: mentioning
confidence: 99%
“…Slit and Robo are also expressed in mature organisms, and an isoform of Robo, Robo-1, was detected on the surface of cells involved in vascular injury, including neutrophils, vascular smooth muscle cells (VSMC), lymphocytes, and monocytes (14)(15)(16)(17)(18)(19). In neuronal cells, Slit2 promotes recruitment of soluble Slit Robo GTPase-activating protein to the cytoplasmic tail of Robo-1, in turn preventing activation of the Rho family GTPases Rac and Cdc42 (20).…”
Section: mentioning
confidence: 99%